2017
DOI: 10.24263/2304-974x-2017-6-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and chemical attributes of dessert wines made by different freezing methods of Marselan grapes

Abstract: Keywords:Icewine Marselan Freezing Northen Black Sea coast. Introduction. The purpose of research was to determine the impact of different freezing methods of Marselan grapes on sensory and physicochemical compositions of obtained icewines.Materials and methods. Sweet wines were obtained by two ways of freezing of Marselan grapes: naturally and alternativecryogenic extraction. The production and physicochemical parameters of wines were conducted in agreement with the provisions of the International Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Aroma compounds are one of the most important groups to determine the level of quality in a wine (Villamor and Ross, 2013;Fariña et al, 2015). The grape variety and the technology used during winemaking are crucial for odor quality in wines (Geffroy et al, 2015;Ostapenko et al, 2017;De Castilhos et al, 2019). 'Marselan' is a red grape variety that resulted of the crossing of 'Cabernet Sauvignon' and 'Grenache' grapevine varieties in Marseille, France.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aroma compounds are one of the most important groups to determine the level of quality in a wine (Villamor and Ross, 2013;Fariña et al, 2015). The grape variety and the technology used during winemaking are crucial for odor quality in wines (Geffroy et al, 2015;Ostapenko et al, 2017;De Castilhos et al, 2019). 'Marselan' is a red grape variety that resulted of the crossing of 'Cabernet Sauvignon' and 'Grenache' grapevine varieties in Marseille, France.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its sensory characteristics, 'Marselan' has become of great importance in new world wine countries, such as China, which has the most 'Marselan' plantings in the world (Ma, 2017;Jiao and Ouijang, 2019;Lyu et al, 2019). Historically, the wine market has expanded when unfamiliar grape varieties are associated with non-traditional elaboration processes (Ostapenko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been reported that Marselan was shown to produce wines with juicy vegetable and spicy aroma characteristics [14]. A few studies focused on the flavor of Marselan wine through analyzing non-volatile components, and malvidin-3-glucoside was the richest anthocyanin-derived pigment component [1,15]. However, as far as we know, the aromatic and chemical characteristics of Marselan wine have rarely been reported with respect to quantitative data for aroma compounds and their aroma contributions.…”
Section: Introductionmentioning
confidence: 99%